Interaction of Ethics and Understanding of Auditor Information Systems in Determining Audit Quality - Titis Puspitaningrum Dewi Kartika; Riski Aprilianita (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: this research to analysis internal and external factors influencing audit quality. Internal factors include independence, competence, understanding of information system and audit ethic. Meanwhile, external factors involve time budget pressure and audit fees. Desigm/methodology/approach: of this study was using survey by distributing questionnaires via online and offline with auditor respondent in Java Island. The respondents are 35 auditors who are spread around Surabaya. Hypothesis testing used regression test and interaction test. Finding: the results in this study were Competence and Independence had a positive effect on Audit Quality; Audit Fee and Time Budget Pressure had no effect on Audit Quality; (Interaction between Auditor Competencies) Auditor Ethics had no effect on Auditor Quality; (Interaction between Auditor Independence) Auditor Ethics had a negative effect on Auditor Quality; (Interaction between Time Budget Pressure) Understanding of Information Systems had no effect on Audit Quality. Research limitation/Implication: in this research only auditor responden in surabaya. Practical Implication: is understand the factors thaht influence audit quality. Originality/value: this reaearch is factors influencing audit quality to auditors in surabaya. Paper type: is research paper